Noetic and Noematic Dimensions of Religious Experience - Barber Michael David (Open Theology, 2020)
Phenomenologies of religious experience have been developed by Max Scheler and via Alfred Schutz’s frameworks of “multiple realities” and “finite provinces of meaning.” For both, religious experience resists the pragmatic imperatives of the mechanistic worldview or world of working. Schutz’s paradigm begins with a distinctive noetic religious epoché opening the religious province, in contrast with Scheler’s start with spheres of being (especially the absolute sphere) furnishing the noematic context for religious acts. Scheler’s religious act resembles the religious epoché, but his eidetic analysis highlights the act’s distinctiveness, irreducibility to non-religious acts, and immunity to psychological reductionism. Correlating the religious act with his value theory (the absolute sphere), Scheler better withstands the subordination of religion to the pragmatic imperatives and the absolute to lesser values than does a Schutzian ranking of purposes in the province’s form of spontaneity. Scheler’s absolute personal being, whose revelation one must respectfully wait, supports the Schutzian relaxed tension of consciousness. Respectfulness of persons, the social/communal/critical dimensions of religious experience, religion’s need for critique from theoretical provinces of meaning, and the wariness of idolatrously substituting one’s own finite goods for the absolute can all mitigate the religious imperialism and violence to which absolute commitments can lead.